Significant therapy events with clients with intellectual disabilities. Issue 5 (1st November 2018) - Wills, Sarah; Robbins, Lorna; Ward, Tony; Christopher, Gary
Abstract : Purpose: The purpose of this paper is to explore significant events in psychotherapy with clients with intellectual disabilities (IDs). Design/methodology/approach: Four therapy dyads, each consisting of one client and one therapist, were recruited. Following the brief structured recall procedure (Elliott and Shapiro, 1988), semi-structured interviews focused on helpful events in psychotherapy, using video of particular sessions as a stimulus to help prompt recall of that session. Findings: Using interpretative phenomenological analysis, five super-ordinate themes were identified: "The Uniqueness of the Therapeutic Relationship"; "Using adaptations to Express Emotions"; "Client Behaviour/Therapist Behaviour"; "Hope and Paternalism"; and "Meaning-Making". The results provide additional evidence that significant therapy events occur for clients with IDs. Furthermore, the research enabled insights to be gained about the process of therapy for this client group and for exploration of therapeutic factors that may be involved in facilitating a significant therapy event. Research limitations/implications: This study highlights the need for therapists to work in such a way as to facilitate significant events in therapy. Whilst this study was a necessary first step, owing to the non-existence of research in this area, the sample size and qualitative design may limit any wider generalisation of the findings. Originality/value: Significant events have not previously been explored in psychotherapy with clients with IDs. This research could therefore make an important contribution to our understanding of the process of psychotherapy for this client group.